ANALISIS ALIRAN DAYA SISTEM KELISTRIKAN 150 KV BALI SAAT REKONDUKTORING SUTT GILIMANUK – NEGARA – ANTOSARI - Huda, M.K.; Ariastina, W.G.; Sukerayasa, I W. (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p11, 2020)
The need for electricity that is growing rapidly on the island of Bali, makes PT PLN (Persero) seek strategic steps in serving customers. Gilimanuk - Negara - Antosari Reconductoring SUTT 150 kV is one of the efforts made by PT PLN (Persero) to improve the reliability of the Bali Electricity System which is used to overcome power evacuation problems in the future. Reconductoring goes through a one-month trip phase in each circuit. For this reason, a study is needed to identify the electricity system readiness by using a power flow analysis simulator application.The simulation is done by extinguishing each of the 150 kV conductors in the Bali Electricity System alternately by taking into account four scenario namely before conducting a reconductor, reconductor circuit 1, reconductor circuit 2, and after reconductor. Voltage recording is carried out on each bus with a tolerance of + 5% Vnom, recording of the load is carried out on each active 150 kV conductor with a maximum capacity of 80% Inom. The results of the simulation show that the anomaly is only obtained when the simulation of circuit 1 reconductor works if SUTT 150 kV Gilimanuk - Celukan Onion trip, causing a load exceeding 80% Inom on SUTT 150 kV Gilimanuk - Pemaron and SUTT Gilimanuk - Negara - Antosari 2.